The Win-Win Philosophy or The Institution of Judicial Mediation in Ukraine and The World - Запара, Світлана (Научни трудове, 2018)
The win-win philosophy reflects the ideology of mutual benefits, the satisfaction of mutual interests, and the conclusion of strategic alliances that is inherent to the mediation institution.Efforts are being made to provide the legislative regulation of mediation in Ukraine.The author’s position is in the need for a comprehensive study of judicial mediation under the judicial reform implementation in Ukraine and the development of the conceptual standpoints of “natural imbedding” of this institution in the national legal system.
Keywords: Медиация; Съдебна медиация; Съдебна реформа